Implementasi Tanggung Jawab Kepolisian Tentang Pengamanan Eksekusi Jaminan Fidusia - Simatupang, Boby Daniel; Negoro, Wahyu Saptha; Ramadhani, Ivo (LPPM Universitas Potensi Utama, 2025)
In the Indonesian Government regulations, Fiduciary has been stated in Law No. 42 of 1999. Where the definition of Fiduciary is a process of transferring ownership of an object based on trust, but the object is still in the control of the party who transferred it. So that the Law becomes a means of creating a community rule that exists for everyone who wants to feel justice so that it becomes the main focus of the formation of legislation that must be in accordance with the principles of justice and the function of law as social control, then this relationship between law and social values ​​is interrelated where law as a solution to problems for society in general. Law has a dual function on the one hand is an action that may be so institutionalized which is then used by society to achieve a goal of solving problems in the responsibility of the police regarding the security of the Execution of Fiduciary Guarantees. The method used in this study is the Applied Research Method, where this method is a type of research whose results can be directly applied to solve the problems being faced. As. Prof. Mr. E.M Meyers who defines Law in his book